Foreign bodies : Oceania and the science of race 1750-1940 - Douglas, Bronwen; Ballard, Chris, 1963- (ANU E Press, 2008)
"The collection investigates the reciprocal significance of Oceania for the science of race, and of racial thinking for Oceania, during the two centuries after 1750, giving 'Oceania' a broad definition that encompasses the Pacific Islands, Australia, New Guinea, New Zealand, and the Malay Archipelago. We aim to denaturalize the modernist scientific concept of race by means of a dual historical strategy: tracking the emergence of the concept in western Europe at the end of the eighteenth century, its subsequent normalization, and its practical deployment in Oceanic contexts; and exposing the tensions, inconsistencies, and instability of rival discourses. Under the broad rubrics of dereifying race and decentring Europe, these essays make several distinctive and innovative contributions. First, they locate the formulation of particular racial theories and the science of race generally at the intersections of metropolitan biology or anthropology and encounters in the field a relatively recent strategy in the history of ideas. We neither dematerialize ideas as purely abstract and discursive nor reduce them to social relations and politics, but ground them personally and circumstantially in embodied human interactions."--Provided by publisher